Integration of ICT in Malaysian secondary schools: What conditions will facilitate its use? - Khalid, Fariza; Nawawi, Mokhtar; Roslan, Samsilah (The International Journal of Learning, 2009)
The integration of information and communication technology or ICT in teaching and learning is an innovation that had revolutionized the educational system. In the Malaysian context, although extensive efforts were made under its school computerizing programme to bring ICT to the secondary school classroom there exist a gap among schools in the use of ICT. What conditions will assist teachers in using ICT in the classroom? This study was carried out to determine the presence or non-presence of the eight conditions suggested by Ely, that when present in the school environment will facilitate the integration of ICT in the teaching and learning process. The participants for the study were 429 teachers from 16 secondary schools who taught several subjects in the Humanities, Languages, Sciences, and Technical areas in the state of Selangor and Kuala Lumpur, the capital city of Malaysia. Data for the study was gathered by the use of a set of questionnaires. The findings of the study, indicated that in general only three of the conditions were found to be most present namely commitment by those involved, leadership and presence of knowledge and skills. The other five conditions namely rewards or incentives, availability of resources, dissatisfaction with the status quo, participation, and time were present at a lesser degree in the schools. The results of correlational analysis among conditions suggest that a strong significant positive relationship exist between conditions “presence of leadership” and “commitment by those involved.” Besides that a moderate significant positive relationship also exists between “presence of leadership” and “availability of resources” and with “participation by those involved.”